Landmark publications in onychology: a bibliometric analysis - Bin Rubaian , Nouf F.; Kashif , Haider; AlHemli , Haya A.; Siddique , Nadeem Siddique; Waris, Abu; Muhammad Ajmal Khan , Muhammad Ajmal; Atreya, Alok; Moizuddin , Khwaja; Mohiuddin , Shamim Shaikh; Menezes, Ritesh G. (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Onychology refers to the study of the various disorders of nails. The present study aimed to determine research productivity and trends in onychology research by analyzing the top 100 articles with the highest citations. Methods: The Web of Science core collection database (WOSCC) was searched by utilizing an advanced search query builder feature that predominantly utilized the TI (title) and (AK) author keywords fields. The top 100 cited documents were retrieved and analyzed for authorship and collaboration patterns, relevant sources of publication, most prolific authors, productive countries, and organizations. Results: ‘Articles” emerged as the most proliferative documents with 81 publications and 9686 citations. The USA emerged as the most productive country with 39 publications. Columbia University and the University of California emerged as the most productive institutions. The ‘Journal of the American Academy of Dermatology’ emerged as the most productive source, with 19 publications. ‘Baran R’ emerged as the most prolific author with 8 publications. The USA emerged as the most collaborative country in the field of onychology, collaborating mainly with the UK, France, Germany, Italy, Canada, and Spain. Conclusions: Bibliometric analysis of research productivity and publication trends in onychology revealed that the USA emerged as the most significant contributor and collaborative country. Contributions from Asian countries were not impressive, possibly due to limited resources of significant healthcare delivery systems and research facilities.(www.actabiomedica.it)